Therapeutic potential of hair follicle-derived stem cell intranasal transplantation in a rat model of ischemic stroke - Mousavi, Seyedeh Maryam (2022)
Background Stem cell-based therapy has received considerable attention as a potential candidate in the treatment of ischemic stroke; however, employing an appropriate type of stem cells and an effective delivery route are still challenging. In the present study, we investigated the therapeutic effect of safe, noninvasive, and brain-targeted intranasal administration of hair follicle-derived stem cells (HFSCs) in a rat model of ischemic stroke. Methods Stem cells were obtained from the adult rat hair follicles. In experiment 1, stroke was induced by 30 min middle cerebral artery occlusion (MCAO) and stem cells were intranasally transplanted immediately after ischemia. In experiment 2, stroke was induced by 120 min MCAO and stem cells were administered 24 h after cerebral ischemia. In all experimental groups, neurological performance, short-term spatial working memory and infarct volume were assessed. Moreover, relative expression of major trophic factors in the striatum and cortex was evaluated by the quantitative PCR technique. The end point of experiment 1 was day 3 and the end point of experiment 2 was day 15. Results In both experiments, intranasal administration of HFSCs improved functional performance and decreased infarct volume compared to the MCAO rats. Furthermore, NeuN and VEGF expression were higher in the transplanted group and stem cell therapy partially prevented BDNF and neurotrophin-3 over-expression induced by cerebral ischemia. Conclusions These findings highlight the curative potential of HFSCs following intranasal transplantation in a rat model of ischemic stroke.